Cystic fibrosis diagnosed in a nineteen-year-old case - Yılmaz, Meltem; Mutlu, Levent (The European Research Journal, 2023)
Cystic fibrosis is the most common autosomal recessive hereditary disease in white populations. It is characterized by the formation of abnormal secretions in the exocrine glands located in the sweat and salivary glands, tracheobronchial tree, large intestine, and pancreas. The severity of the clinic depends on the type of "cystic fibrosis transmembrane regulatory protein" gene mutation. Although most cases are diagnosed in infancy or childhood, some patients are also diagnosed during adolescence and adulthood. We report a case of a 19-year-old patient who was followed up with a diagnosis of asthma and bronchiectasis since childhood and diagnosed with cystic fibrosis.